A non‐crimp fabric mechanical characterization for the production of aerospace components. Issue 5 (30th March 2021) - Lepore, Marcello A.; Ferrante, Luca; Sanguigno, Luigi; Maligno, Angelo R.
Abstract: This work shows a procedure for the mechanical characterization of a new composite for aerospace. Initially, a preliminary test campaign has been carried out to identify the most suitable fabric and resin for the production of the new composite. Subsequently, the production of the composite plaques has been planned. Then, plaques with different orientation of the layers and thicknesses have been obtained. From each of these plaques' coupons for the experimental tests, needed to the mechanical characterization of the composite, have been obtained. The experimental tests have been carried out in a certified laboratory with electromechanical machines and according to ASTM standards. For each experimental test, the trend of the stress–strain curves has shown a typical behavior up to failure. An analysis of the coefficient of variation, based on the statistical mean of parameters calculated with the experimental tests, has been carried out to evaluate the reproducibility of the tests in different laboratories.